Chalcones and Carbon Dots as Emerging Breakthroughs in Glioblastoma Multiforme Treatment - Travieso, Erika (Journal of Student Research, 2023)
Glioblastoma Multiforme (GBM) is a very aggressive brain tumor that is resistant to treatment and has a diverse population of genetically unstable, deeply infiltrating cells. Although significant efforts have been made to find new anti-GBM drugs, these efforts have largely been unsuccessful in human trials because of problems with effectiveness, selectivity, or physicochemical properties. The successful eradication of GBM stem cells (GSCs) is of high priority because GBM stem cells are in charge of patient relapse and tumor regrowth after therapy. The analysis of five published science journals has led to the conclusion that utilizing chalcones as the treatment for Glioblastoma and carbon dots as the carriers could change the approach to curing Glioblastoma. All of the authors examined have either conducted research with chalcones and carbon dots, or have reported their effectiveness from other published papers. The purpose of this paper will be to bring awareness to the potential of chalcones and carbon dots, seeing as they have been scarcely mentioned in the literature regarding Glioblastoma research.